The Expansion Segments of Human 28S rRNA Match MicroRNAs Much Above 18S rRNA or Core Segments - Parker, Michael S.; Balasubramaniam, Ambikaipakan; Parker, Steven L. (MicroRNA, 2018)
Background: The size of eukaryotic 25-28S rRNAs shows a progressive phylogenetically linked increase which is pronounced in mammals, and especially in hominids. The increase is confined to specific expansion segments, inserted at points that are highly conserved from yeast to man. These segments also show a progressive increase in nucleotide bias, mostly the GC bias. Substantial parts of the large expansion segments 7, 15 and 27 of 28S rRNA are known to be exposed at the ribosome surface, with no clear association with ribosomal proteins. These segments could bind extraneous RNAs and proteins to support regulatory events. Methods: This study examined the possible canonical matching of human 28S rRNA and 18S rRNA segments with 2586 human microRNAs. This was compared with matching of the microRNAs to sectors of 18810 human mRNAs. Results: The overall matching was rather similar across 18S rRNA segments and core segments of 28S rRNA. However, the expansion segments of 28S rRNA (abbreviated ESL) collectively have a much higher (up to two-fold) capacity for the canonical association with microRNAs. This is pronounced in large ESL, and is found to strongly relate to the GC content of microRNAs. Conclusion: Oligonucleotides and microRNAs of high GC content through a strong canonical hydrogen bonding could have large activity in regulation of subcellular RNAs. In view of the considerable abundance of ribosomal RNAs in many mammalian tissues, ESL could constitute an important component of microRNA balance, possibly serving to lower the availability of GC-rich microRNAs (and thereby help conservation of GC-rich mRNAs).
Keywords: expansion segments